Interaction between plant characters in peanut (Arachis hypogaea L.) and the expression level of the cucumopine synthase gene - V. D. Bemova; E. A. Porokhovinova; T. V. Yakusheva; L. P. Podolnaya; V. A. Gavrilova (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Peanut is a valuable crop for agriculture. Studies have shown that peanut is a naturally transgenic plant: its genome contains T-DNA, called cellular (cT-DNA), obtained during evolution from agrobacteria. The cus gene encodes cucumopine synthase, responsible for the synthesis of cucumopine. This gene was earlier proven to be intact in peanut and actively expressed in plant organs, but its effect is still unknown. We attempted to analyze important agronomic characters in a set of peanut accessions and find correlations between their manifestation and the cus gene expression level.Materials and methods. The study involved 63 peanut (Arachis hypogaea L.) accessions from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). For 10 of them, the results of the analysis of the cus gene expression level in different organs were obtained. Ecogeographic tests were performed in 2019–2021 at two sites: the Kuban Experiment Station of VIR, and the Caspian Agrarian Federal Research Center. The indicators were described in accordance with the guidelines. The fatty acid composition in seeds was assessed using gas chromatography, while the protein content was measured using the Kjeldahl method. Statistica 7.0 software was employed for statistical data processing.Results and conclusion. Variability assessment of important agronomic characters studied during three years of ecogeographic tests, the Mann-Whitney U-test, and the factor analysis of principal components were applied to clarify the interplay of these characters with the expression level of the cus gene in different organs of peanut plants. The findings of this study disclosed some trends suggesting that a high level of the cus gene expression affected the productivity indicators in peanut.